CAMPUR KODE DALAM KOMIK GENTE ~RISUTORANTE NO HITOBITO~ JILID 1 DAN 2 KARYA ONO NATSUME - TAMARA, DWINDA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Code, Mix Code, Comic Language is use for communicate idea and opinion so the listener can understand what is speaker’s says. Although in daily life, we often find people talking with foreign language insertion in their utterance. It is same with cartoonist when create comic they also inserting foreign language in their comic dialog. For example Gente~Ristorante no Hitobito~ comic written by Ono Natsume. Writer thought that is something interesting and decide to research mix code. The problems will be investigate: What are types, kinds, and mix code factors which used by restaurant staff and regular customer in Gente~Risutorante no Hitobito~ comic volume 1 and 2 written by Ono Natsume?  Writer use qualitative description research metode. Data source in this research is Gente~Risutorante no Hitobito~ volume 1 and 2 written by Ono Natsume. Total data obtained from data source is 152 mix codes.From this research had been found: 70 outer code mixings, 58 words, 8 phrases, and 15 expressions. The dominant factors of mix code in comic Gente~Risutorante no Hitobito~ volume 1 and 2: lexical needs, to limit conversation with another listener. Side factors of mix code in Gente~Risutorante no Hitobito~ comic volume 1 and 2: (1) setting and scene, (2) end, (3) key,and (4) instrumentalis.